اسلام کا نظام عفت وعصمت : ایک مطالعہ: A Study of Islamic System of Chastity and Infallibility (Al-Qamar, 2020)
The great aspect of human life on which its survival depends is the protection of chastity. One of the five purposes of Shariah (Maqāsid-e-Sharī̒ah) is the protection of chastity. The following are the sources of protection of chastity in Islam, such as, Piety and fear of God, Timely marriage, Collective sponsorship of the poor and needy, Fasting, Implementation of Islamic laws (Hudud) and punishments. On crimes which leads to vulgarity as, malice aforethought evil eyes, Free relationship of men and women in society, delaying of marriage despite Affordability, Considering marriage with widows as defective.
Keywords: Chastity and Infallibility; Islamic Laws; Women